"Effect of modified aramid nanofiber on compatibilization of natural rubber/epoxidized natural rubber composites" - ZHANG Ke-yu1,2, ZHENG Xiao-tong1, XU Ming-han1?鄢 (Hecheng xiangjiao gongye)
"The combination of natural rubber (NR) with epoxidized natural rubber (ENR) could improve the wet slid resistance, mechanical properties, abrasion resistance and thermo-oxidative aging resistance of NR, which showed important research significance. Aramid nanofiber, as a new nano filler for polymer developed in recent years, had the advantages of both macroscopic fibers and polymer nanomaterials. The NR/ENR composites were prepared by dry mixing with NR and the pre-composite prepared from ENR latex and the modified aramid nanofibers (t-ANF). The influences of ENR and t-ANF on the properties of NR were studied. The results showed that t-ANF improved significantly the phase separation of ENR in NR, and in the meanwhile enhanced effectively the dispersion of silica in the NR/ENR composites. Moreover, the addition of ENR/t-ANF improved the wet slid resistance of NR. This strategy provided theoretical and experimental basis for realizing the dispersion of silica in rubber matrix and improving the compatibility between ENR and NR. SEM images of NR, different NR/ENRx and NR/ENRx/t-ANFy composites, where x represented the amount of ENR in NR/ENR and NR/ENR/t-ANF composites, and y represented the amount of t-ANF in NR/ENR/t-ANF composites, were shown in Fig 1. As shown in Fig 1b and 1c, silica dispersed uniformly with the addition of ENR to the system. However, when the amount of ENR in the NR/ENR composites was increased up to 15 phr （mass, similarly hereinafter）, agglomerations were presented due to the poor compatibility between NR and ENR. In comparison, the silica dispersion was more uniformly by loading t-ANF, and the best dispersion of the NR/ENR/t-ANF composites was achieved when the addition amount of the pre-composite ENR/t-ANF with m(ENR)/m(t-ANF) of 10/1.11 was 11.11 phr. The peak of loss factor (tan δ) became wider after the filling of ENR as shown in Fig 2. A new peak appeared at -28.9 ℃ when the amount of ENR was up to 15 phr, indicating that phase separation occured within the NR/ENR composites. In comparison, t-ANF prevented the phase separation of the NR/ENR composites. The intensity of the second tan δ peak of the composites decreased by the incorporation of t-ANF, revealing the improvement of the compatibility between ENR and NR. Meantime, t-ANF increased tan δ of NR/ENR composites at 0 ℃ which indicated the enhancement of the wet slid resistance. Correspondingly, the loading of a small amount of t-ANF (0.56 phr) would not increase the rolling resistance of the composites as the same tan δ of the composite at 60 ℃ was obtained."